Aortic coarctation and associated cardiac lesions – optimal therapeutic approach: report of 2 cases - Velinovic, Milos; Karan, Radmila; Kovačević-Kostić, Nataša; Obrenović-Kirćanski, Biljana; Vraneš-Stojimirov, Milica; Milićević, Vladimir; Nikolić, Dejan; Milić, Dragan (Vojnosanitetski pregled, 2021)
Abstract Introduction. Aortic coarcation is a congenital condition mostly detected and treated during childhood. Adult patients with coarctation and associated cardiac lesions represent a challenge and a subject of debates concerning adequate treatment. We report 2 patients with aortic coartation when a surgical treatment was necessary. Case report. First patient was a 61-year-old male with previous mechanical aortic valve implantation. He underwent one stage surgical reconstruction of aortic coarctation and surgical repair of aneurysm of ascending aorta. The second patient was a 49-year-old female with aortic aneurysm, bicuspid aortic valve, severe aortic insufficiency and coarctation of aorta below branching of subclavian artery. She underwent the Bentall procedure and surgical repair of coarctation by bypass where the proximal anastomosis was made between the terminal part of Dacron graft and the lateral part of graft used for Bentall, while the distal anastomosis was made between the terminal part of Dacron graft and the lateral part of descending aorta below coarctation. The postoperative course and the follow-up of the patients of 3 and 1 year, respectively, were without complications. Conclusion. Single operation is a better choice in the patients with concomitant pathology such as the aortic aneurysm, or aortic valve disease. Each patient should be analyzed on a single basis, and a decision about a surgical technique and surgical course brought accordingly.